2016 IEEE Congress on Evolutionary Computation (CEC) 2016
DOI: 10.1109/cec.2016.7744320
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of constraint-handling techniques in evolutionary constrained multiobjective optimization

Abstract: Solving constrained multiobjective optimization problems is one of the most challenging areas in the evolutionary computation research community. To solve a constrained multiobjective optimization problem, an algorithm should tackle the objective functions and the constraints simultaneously. As a result, many constraint-handling techniques have been proposed. However, most of the existing constraint-handling techniques are developed to solve test instances (e.g., CTPs) with low dimension and large feasible reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 22 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…More recent variants of this framework have been proposed (e.g. NCTP [18]), but the shortcomings mentioned previously remain.…”
Section: Related Work a Constrained Multi-objective Optimizationmentioning
confidence: 99%
“…More recent variants of this framework have been proposed (e.g. NCTP [18]), but the shortcomings mentioned previously remain.…”
Section: Related Work a Constrained Multi-objective Optimizationmentioning
confidence: 99%
“…Test problems play a crucial role in judging whether an algorithm is a candidate for solving MOPs [3]- [4]. Currently, test instances for DMOPs [3]- [5], [63] and CMOPs [6], [31], [48] have been proposed. However, these test problems do not consider dynamism and constraints simultaneously.…”
Section: Proposed Test Problemsmentioning
confidence: 99%
“…Designing test problems with trigonometric functions can easily reflect these characteristics arising in real-world problems by adjusting the corresponding parameters. Based on the above discussions and benchmarks designed in [4], [6], and [48], this study proposes the following instance generator.…”
Section: Proposed Test Problemsmentioning
confidence: 99%
“…Normally, there should be four combinations altogether, i.e., Deb's feasibility-based rule and ε constrained method in the first and second phase, named D-E, D-D, E-E, E-D respectively. In [11], the first three combinations are compared, and this paper will further study the fourth combination (C 2 oDE-ED), i.e., ε constrained method in the first phase and Deb's feasibilitybased rule in the second phase.…”
Section: General Model For Comparisonmentioning
confidence: 99%
“…Mezura-Montes et al [10] proposed a simple combination of two DE variants (i.e., DE/rand/1/bin and DE/best/1/bin) based on the empirical analysis of four DE variants. Li et al [11] suggested more experimental comparisons on different constraint-handling techniques are needed. They compared three representative constrainthandling techniques (i.e., Constrained-domination Principle, Self-adaptive Penalty, and Adaptive Tradeoff Model), and the search algorithm is nondominated sorting genetic algorithm II (NSGA II).…”
Section: Introductionmentioning
confidence: 99%